Pengembangan Komposit Dari Karet Ebonit Dengan Penguat Serat Bambu Untuk Komponen Otomotif Penutup Spion Sepeda Motor - Mulyanto, Ade; , Joko Sedyono, ST., M.Eng., Ph.D; , Bambang Waluyo F, ST. MT (2016)
This study aims to determine the maximum tensile strength of bamboo fiber with NaOH treatment and to determine the tensile strength, izod impact, violence against variation of composite fiber weight fraction and know the type of fault with observation macro photo of tensile and Izod impact testing. The manufacture of composite materials used are bamboo fiber as reinforcement and ebonite as a matrix. Soaking process using NaOH 5% variation soaking for 0, 2, 4, and 6 hours. By using the standard test ASTM 3379-75 Furthermore, the process of mixing natural rubber with chemicals using the machine two roll mill and then vulcanized by using a mold press. Testing composite using ASTM D638-02 for tensile test, ASTM D256-00 for Izod impact test, ISO 0778-09 for hardness test and macro photo. The results obtained fiber tensile strength of the highest average in the variation 5% NaOH soaking for 2 hours at 203,667 MPa. The voltage on the composite ebonite highest average with 40 phr of bamboo fibers in the fracture at 6,217 MPa, at the highest strain in the composite average ebonite bamboo fiber 20 phr at 50,6%, for the highest modulus of elasticity of the average fracture ebonite bamboo fiber composite 40 phr amounted at 40,657 Mpa, the highest price of the average izod impact on bamboo fiber composite ebonite 40 phr at 1,492J / mm² and the highest hardness to the composite average ebonite bamboo fiber 20 phr shore A scale at 92,66. Based on the analysis results in the fracture Izod impact test and tensile test the type of fault that occurred was the fault of clay.